Numerical simulation of thermal stress fluctuation at a mixing tee for thermal fatigue problems - Koji MIYOSHI; Akira NAKAMURA; Yoichi UTANOHARA; Masayuki KAMAYA (Mechanical Engineering Journal, 2018)
Thermal fatigue cracks have been found at mixing tees in nuclear power plants. The mixing flow of high and low temperature fluids causes temperature and stress fluctuations in the pipe wall and these result in fatigue crack initiation. The authors have conducted a fluid-structure coupled simulation to estimate the fluid and pipe wall temperatures in a mixing tee in their previous study. In the present study, the authors simulated thermal stress using the previous simulation results of the pipe wall temperature. The simulated thermal stress was validated using the stress obtained from the temperature on the pipe inner surface measured by mock-up tests. The test section of the tee pipe was made of stainless steel and consisted of a horizontal main pipe with a diameter of 150 mm and a T-junction connected to a vertical pipe with a diameter of 50 mm. The ranges of the large temperature and stress fluctuation areas on the pipe inner surface calculated by the fluid-structure coupled simulation were narrower in the axial direction of main pipe compared with the results of test. On the other hand, the profiles of the circumferential direction were reproduced by the fluid-structure coupled simulation. The maximum values of the temperature and stress fluctuation ranges were overestimated. The stress fluctuation obtained from the measured temperature showed the equibiaxial behavior where the axial and circumferential stresses had a proportional relationship. Such characteristics of stress fluctuation were reproduced well by the numerical simulation. Not only the stress fluctuation range but also the number of cycles for the stress amplitude were estimated using the time history of the thermal stress and the rain-flow counting method. The distribution of the number of cycles for the stress amplitude estimated by the simulation was similar to that obtained from the measured temperatures.